Central nervous system tumour in pregnancy, a diagnostic challenge or management quandary - Abd Malik, Nur Rashidah; Ali Yeon, Amira Anis; Ismail, Hamizah; Mohd Rashid, Nurul Nafizah; Wahab, Mohd Ghaddafi; Awang, Mohamed Saufi (International Islamic University Malaysia (IIUM), 2026)
Central nervous system (CNS) tumour, being rare in pregnancy, posed different challenges. We report three challenging cases managed at our centre. The first case was a diagnostic puzzle, bringing a myriad of differentials since the eighth week of gestation. Diagnosis made after magnetic resonance imaging (MRI) post-delivery at 35 weeks of gestation led to cervical spine meningioma excision surgery and subsequent progressive, remarkable neurologic recovery. Two additional cases were not a diagnostic mystery, yet they posed management challenges. The second case was diagnosed with a cerebellar tumour complicated with hydrocephalus at a pre-viable gestation. Pregnancy was able to be prolonged up to viability at extreme prematurity at 26 weeks when she needed delivery with subsequent cerebellar haemangioma excision and recovery. However, the third case became pregnant during follow-up after radiation therapy for brain glioma, with persistent symptoms necessitating termination of pregnancy.